2014
DOI: 10.1155/2014/853159
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Changes in the Macroscopic Morphology and Microarchitecture of Denervated Long Bone Tissue after Spinal Cord Injury in Rats

Abstract: To study the effects of mechanical loading on bones after SCI, we assessed macro- and microscopic anatomy in rats submitted to passive standing (PS) and electrical stimulation (ES). The study design was based on two main groups of juvenile male Wistar rats with SCI: one was followed for 33 days with therapies starting at day 3 and the other was followed for 63 days with therapies starting at day 33. Both groups were composed of four subgroups (n = 10/group): (1) Sham, (2) SCI, (3) SCI + PS, and (4) SCI + ES. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Later in 1997 Edoff et al 15 concluded that after dissection of the sciatic and the saphenous nerve, the length of metatarsal bones in immature rats was shorter compared to the normal ones. 17 years later, Zamarioli et al 18 concluded that after provoking spinal cord injury, both macroscopic as well as microscopic structures of the bone are altered.…”
Section: Discussionmentioning
confidence: 99%
“…Later in 1997 Edoff et al 15 concluded that after dissection of the sciatic and the saphenous nerve, the length of metatarsal bones in immature rats was shorter compared to the normal ones. 17 years later, Zamarioli et al 18 concluded that after provoking spinal cord injury, both macroscopic as well as microscopic structures of the bone are altered.…”
Section: Discussionmentioning
confidence: 99%
“…Bone loss after neurologic injury is postulated to be multifactorial: severe immobilization and loss of weight loading related to paralysis, 4,5 sensory and sympathetic denervation of the bone, 6,7 loss of anabolic factors (ie, testosterone, growth hormone), 8 presence of catabolic factors (systemic inflammation, administration of drugs like steroids at the time of injury), 9 other factors locally influencing bone metabolism (ie, paracrine influences from atrophied muscles), 10 and chronic administration of drugs known to negatively affect bone metabolism (antidepressants, anticonvulsivants, opioids, proton pump inhibitors, anticoagulants). 11 Bone loss is dependent on time from and extent of neurologic injury, with most bone loss occurring in the first year after complete motor paralysis.…”
Section: Bone Loss In Sci/d-related Paralysismentioning
confidence: 99%
“…23 Although frequencies ranging from 20 to 70 Hz are recommended to ensure participant safety, 24 Hadi et al 25 demonstrated previously that subjects with SCI preferred high-frequency vibration.…”
Section: Wbv Therapymentioning
confidence: 99%
“…Thus, the authors believe that ES should be included in the rehabilitative program of SCI individuals to improve muscle health and also bone quality, because of osteogenic effects of muscle contraction on the bone tissue. 15,23,36,37 …”
Section: Figurementioning
confidence: 99%